2014
DOI: 10.1074/jbc.m114.567685
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Heme Oxygenase-1 (HO-1) Modulates Subcellular Distribution and Activation of Nrf2, Impacting Metabolic and Anti-oxidant Defenses

Abstract: Background: A 28-kDa HO-1 isoform is induced by oxidative stress and cancer and accumulates in the nucleus. Results: Nuclear HO-1 interacts with Nrf2 and alters expression of its target genes. Conclusion: HO-1 modulates Nrf2 function. Significance: Exploiting the synergistic benefits of the HO-1⅐Nrf2 protein complex is important for developing therapeutic strategies against oxidative stress or cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
169
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 207 publications
(180 citation statements)
references
References 58 publications
10
169
0
1
Order By: Relevance
“…Based on the fact that cytosolic HO-1 is able to translocate into the nuclei of certain tumor cells [75][76][77], it is possible that HO-1 could directly act as a transcription suppressor or indirectly regulate some transcription factors to inhibit ATF4 expression. It has been reported that HO-1 modulates subcellular distribution and activation of Nrf2 [75], suggesting HO-1 is able to influence the activity of certain transcription factors. However, in our study, HO-1 seems to be located only in the cytosol, excluding its effect in the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the fact that cytosolic HO-1 is able to translocate into the nuclei of certain tumor cells [75][76][77], it is possible that HO-1 could directly act as a transcription suppressor or indirectly regulate some transcription factors to inhibit ATF4 expression. It has been reported that HO-1 modulates subcellular distribution and activation of Nrf2 [75], suggesting HO-1 is able to influence the activity of certain transcription factors. However, in our study, HO-1 seems to be located only in the cytosol, excluding its effect in the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages are resistant to relatively high concentrations of heme in comparison to endothelial cells, and have constitutively high expression of heme oxygenase 1 (HMOX1) to protect against heme toxicity (14,15). As an antioxidant stress protein, HMOX1 is expressed in almost all cells and tissues, and is highly upregulated by heme or other stress stimuli to provide protection against oxidative damage and apoptosis (16).…”
mentioning
confidence: 99%
“…As an antioxidant stress protein, HMOX1 is expressed in almost all cells and tissues, and is highly upregulated by heme or other stress stimuli to provide protection against oxidative damage and apoptosis (16). This is a protective and adaptive response inherent to most tissues (14). The cytoprotective effects of HMOX1 have been attributed to its enzymatic action in heme degradation and also its catalytic byproducts such as carbon monoxide and biliverdin (17).…”
mentioning
confidence: 99%
“…HO-1 is an antioxidative enzyme (14) but may also act independently of enzymatic activity, via interaction with several nuclear proteins (13). As HO-1 was present both in cytoplasm and nucleus of RMS cells (Fig.…”
Section: Effect Of Oxidative Stress On Expression Of Mir-206mentioning
confidence: 99%
“…HO-1 degrades heme to produce biliverdin, ferrous ion and carbon monoxide (CO) or can act trough protein-protein interaction with Nrf2 transcription factor (13,14). The mechanism underlying the antimyogenic effect of HO-1 in myoblasts is CO-dependent inhibition of C/EBPd binding to the myoD promoter that decreases myoD expression.…”
Section: Introductionmentioning
confidence: 99%